The bumiputera policy and "dayakism": an interpretation - Mason, Richard; Jawan, Jayum (Penerbit Universiti Sains Malaysia, 2003)
This paper is an interpretative account of "dayakisrn" over the past four decades following the formation of Malaysia. The paper does not pretend to be comprehensive. It is meant to be no more than an overview of the principal developments in Sarawak politics related to the Dayak and to interpret the disjuncture between "dayakism" and "bumiputeraism" during the recent past